McDowell, Hegel, and Habits. Issue 2 (4th September 2015) - Levine, Steven
Abstract : In his debate with Dreyfus McDowell defends the 'pervasiveness thesis', the thesis that rational mindedness pervades the lives of rational animals, their perceptual experiences and exercises of agency. To counter this idea, Dreyfus introduces the notion of 'social standing': the culturally inculcated yet non-conceptual sense of the appropriate distance that one should stand from another person. McDowell claims that social standing is not a counter-example to the pervasiveness thesis because it stands altogether outside of it. In this paper I argue that this response is a misstep, that we should see social standing as falling within the pervasiveness thesis. While such phenomena do not normally fall within the scope of a subject's practical self- knowledge they are still pervaded by rational mindedness. They are because the dispositions and habits that comprise our second nature, although not the realization of an exercise of conceptual capacities, can be brought within the scope of a subject's practical self-knowledge and in fact changed, and this is enough to establish that they are pervaded by rational mindedness. I argue that we can find a picture like this in a Hegelian-pragmatist account of our habitual second nature.